PENGEMBANGAN ALAT UKUR DIGITAL PANJANG DAN TINGGI BADAN ANAK BALITA UNTUK PENETAPAN STATUS GIZI ANAK DI DAERAH TERPENCIL WILAYAH BOGOR - Soekatri, Moesijanti Y.E.; Marwazi, Hendra; Sambiono, Andy; Nareswara, Anastu Regita; Azkatu R, Asa (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2024)
Determining the nutritional status of children under five depends heavily on accurate measurement results and the measuring instruments used. This study aims to develop a digital length and height measuring instrument for children under five who are able to measure automatically with an accuracy of 0.1 cm and store results up to 100 children's data. This tool uses a VL53L0X sensor and displays nutritional status directly based on WHO 2006 standards (TB/U). A total of 43 children under five were measured using digital and manual tools. The test results showed that the Technical Error of Measurement (TEM) and reliability values on the digital tool were in the “almost perfect” category (≥0.8), similar to the manual tool. Paired-Samples T-Test results showed no significant difference between the two tools (p>0.05). The digital measurement tool also showed high sensitivity and specificity in detecting nutritional status. Therefore, this tool can be used as a practical alternative in anthropometric measurements in remote areas.